2008
DOI: 10.1038/ijo.2008.58
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation to lactation in OLETF rats lacking CCK-1 receptors: body weight, fat tissues, leptin and oxytocin

Abstract: Objective: To understand the adaptation to lactation of obese rats, by studying the interplay among the gut hormone cholecystokinin (CCK), the adiposity hormone leptin and the affiliation hormone oxytocin in modulating body mass and fat storage. Design: Strain differences were examined between Otsuka Long Evans Tokushima Fatty (OLETF) rats lacking expression of functional CCK-1 receptors and Long Evans Tokushima Otsuka (LETO) controls, tested as nulliparous dams, at the 7 and 15th lactation day, at weaning (la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 60 publications
1
13
0
Order By: Relevance
“…Interestingly, whereas OLETF dams gained significantly more weight during pregnancy, the lactating period represented a time point where OLETF females gradually lost weight, almost reaching weight levels of LETO dams at the time of weaning. We have recently reported that this weight loss throughout lactation is accompanied by a decrease in fat stores, adipocyte cell size, and leptin levels (49). We can only speculate about why OLETF females do not maintain a relative hyperphagia beyond that shown by lactating controls during such an energy-demanding period.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Interestingly, whereas OLETF dams gained significantly more weight during pregnancy, the lactating period represented a time point where OLETF females gradually lost weight, almost reaching weight levels of LETO dams at the time of weaning. We have recently reported that this weight loss throughout lactation is accompanied by a decrease in fat stores, adipocyte cell size, and leptin levels (49). We can only speculate about why OLETF females do not maintain a relative hyperphagia beyond that shown by lactating controls during such an energy-demanding period.…”
Section: Discussionmentioning
confidence: 88%
“…Representative cells chosen presented a smooth and clear membrane, with no granulation around. A similar methodological approach was described elsewhere (31,49). The estimated number of cells per fat pad was calculated with the average cell diameter, a density conversion factor (0.915 g/cc), and the mass of the fat pads, as previously described (3,32).…”
Section: Histologymentioning
confidence: 99%
See 1 more Smart Citation
“…Representative cells chosen presented a smooth and clear membrane, without surrounding granulations. A similar methodological approach was described elsewhere (31,57). The estimated number of cells per fat pad was calculated using the average diameter, a density conversion factor (0.915 g/cc), and the mass of the fat pads, as previously described (3,32).…”
Section: Histologymentioning
confidence: 99%
“…OT is a neuropeptide predominantly synthesized within magnocellular neurons of the hypothalamus, but also in some peripheral tissues, including the reproductive system, heart, and bone [2]. OT secretion is modulated by several factors, including estrogens, testosterone, and leptin [2][3][4]. Subcutaneous OT injection reverses bone loss in ovariectomized mice, and enhances bone microarchitecture and biomechanical strength [5].…”
Section: Introductionmentioning
confidence: 99%